Impact of breast cancer cells´ secretome on the brain metastatic niche remodeling. (February 2020) - Carvalho, R.; Paredes, J.; Ribeiro, A.S.
Abstract: Brain metastases occur in approximately 10–20% of patients with metastatic breast cancer showing a very poor overall survival. Curiously, different molecular subtypes (that show specific gene expression signatures and differential prognostic significance) are associated with different risks for brain metastases development, suggesting that cancer cells harbor specific molecular programs that award them intrinsic advantages to survive in this specific foreign tissue. Emerging data has been revealing that biophysical and/or mechanical properties of the brain extracellular matrix (ECM), along with those of the brain resident cells, play a crucial role in creating the best conditions for survival, colonization and outgrowth of breast cancer cells in this distinct microenvironment. Although several reports show that cancer cells modulate metastatic niches way before they reach the target organ, few data exist for the brain metastatic niche. Indeed, little is known concerning how factors secreted by cancer cells activate brain resident cells and/or modify brain ECM biomechanical properties and how these modifications impact cells´ ability to metastasize the brain. The brain is a particular organ, protected by the blood brain barrier (BBB), and containing exclusive functional units and very special cell types. Additionally, it is the organ with the most singular ECM and biomechanical properties. Thus, this cancer cell-brain metastatic niche interaction must present distinct properties. Consequently, the search for putative molecular markers that modulate the brain pre-metastatic niche, thus promoting the successful metastatic homing of cancer cells, is urgently needed. In this review, we will discuss key aspects regarding breast cancer cells and the brain pre-metastatic niche paracrine communication that is crucial to initiate the metastatic cascade. We will focus on cancer cell`s secretome influence into the brain microenvironment, specifically on its impact on tissue mechanics and on brain resident cells as regulators of the pre-metastatic niche formation, ultimately promoting metastatic colonization.